Exploring the Determinants of Intrauterine Device Acceptance in Family Planning in Kolaka, 2024 - Permatasari, Andi Ita; Yusran, Sartiah; Jufri, Nurnashriana; Andajani, Sari (Atlantis Press International BV, 2025)
The usage of intrauterine devices (IUDs) as a long-term contraceptive method remains low in Kolaka Regency. This study aims to analyze the determinants influencing family planning acceptors’ interest in IUD usage, focusing on factors such as knowledge, attitudes, spousal support, number of children, and the availability of health facilities. An analytical cross-sectional design was employed, involving 185 women as research subjects. Data were collected through structured interviews using a questionnaire to assess the relevant factors. The findings reveal that attitude, spousal support, number of children, and health facility availability significantly impact family planning acceptors’ interest in IUDs, with a p-value < 0.05. Among these, spousal support was the most influential variable, exhibiting an odds ratio (OR) of 87.127, followed by attitude (OR = 6.559) and education (OR = 2.932). The number of children had the smallest effect, with an OR of 0.237. In conclusion, attitude, spousal support, number of children, and health facilities are key determinants of family planning acceptors’ interest in IUD use in Kolaka Regency in 2024. To enhance IUD adoption, it is recommended that the Family Planning Coordination Board (BKKB) of Kolaka Regency strengthen health promotion efforts regarding IUD usage among mothers and women of childbearing age.
Keywords: 3215 Reproductive Medicine; 32 Biomedical and Clinical Sciences; 4206 Public Health; 42 Health Sciences; Health Services; Clinical Research; Pediatric; Contraception/Reproduction; Prevention; 3 Good Health and Well Being; IUD; Kolaka Regency; Spousal Support; Women of Childbearing Age; Family Planning